Research on Early Warning Method of Plough Layer Thickness of Cultivated Land in Black Soil Driven by Rainfall Events - Yang, Ning; Pan, Yuchun; Zhou, Yanbing; Liu, Changhua; Gao, Yunbing (International Journal of Natural Resources and Environmental Studies, 2024)
The thinning of the arable layer causes soil quality degradation, seriously affecting crop growth and even threatening national food security. This article focuses on the problems and needs of poor timeliness, high cost, and inability to dynamically warn about the thinning of the tillage layer in black soil farmland, and conducts research on corresponding warning methods. Based on daily rainfall data, the percentile method is used to calculate the threshold for erosive rainfall event driven warning. Based on erosive rainfall event driven coupling of external soil erosion stress meteorological elements and influencing processes, as well as the connotation of geographic events, the concept definition of geographic events for thinning warning of arable layer thickness is given. The semantic description and discovery method of geographic events are provided, and geographic event driven rules and the technical process of thinning warning of arable layer thickness are formulated. There is a significant correlation between rainfall and topsoil thickness, with a correlation coefficient of 0.83. A soil thickness thinning warning simulation was conducted based on the daily rainfall data of Hailun City, Heilongjiang Province in 2020. On June 14, 2020, when the daily rainfall exceeded the event threshold, an automatic warning for thinning of the plow layer was triggered, achieving a dynamic warning process for thinning of the plow layer. The research results indicate that this method is helpful in solving the problem of thinning warning of the cultivated layer thickness in black soil farmland, and can provide technical support for the quality construction, protection, and management of black soil farmland.